Prioritering, profilering og politisk orientering. Engagement og aktivisme i dansk udviklings- og bistandspolitik 1962-2015 - Olesen, Thorsten Borring (Politik, 2015)
Since the late 1970s Denmark has persistently belonged to the small group of states honouring the UN goal for rich countries to donate at least 0,7 per cent of GNP yearly in o cial development aid. is approach has allowed Denmark to pursue an activist policy both multilaterally within international development institutions such as the World Bank, DAC, UNDP, etc. and bilaterally in relation to development countries where Danida, the central Danish aid organization, has been active. Development aid activism and inter- nationalism reached a zenith in the decade after the fall of the Berlin wall when Danish ODA passed the 1 per cent threshold and when the aid component under the heading of „active multilateralism“ was sought integrated into all dimensions of Danish foreign policy. is trend was reversed in the period after 2001 when the Liberal Fogh Rasmussen government took o ce backed by the development aid sceptics in the Danish People’s Party. Critics even maintain that Danish development has seen change resembling a paradigm shift in the post-2001 period. e problem, however, is complex and therefore, on the basis of an analysis of the prioritizing, the orientation and the international pro ling of Danish development aid, this article seeks to disentangle and discuss continuities and break in the role of development aid in Danish foreign policy since the adoption of the rst Danish development aid law in 1962.